16S rRNA Gene Amplicon Sequence Data from Feces of Five Species of Wild Animals in Japan - Ishida-Kuroki, Kasumi; Takeshita, Nachiko; Nitta, Yoshihiro; Chuma, Takehisa; Maeda, Ken; Shimoda, Hiroshi; Takano, Ai; Sekizaki, Tsutomu (Microbiology resource announcements, 2020)
We report 16S rRNA amplicon sequence data from feces from 58 wild boars, 60 feral raccoons, 9 wild Japanese badgers, 21 wild masked palm civets, and 8 wild raccoon dogs in Japan. The predominant bacterial taxa in the fecal microbiota were similar in part but varied among the animal species. We report 16S rRNA amplicon sequence data from feces from 58 wild boars, 60 feral raccoons, 9 wild Japanese badgers, 21 wild masked palm civets, and 8 wild raccoon dogs in Japan. The predominant bacterial taxa in the fecal microbiota were similar in part but varied among the animal species.